1996
DOI: 10.1523/jneurosci.16-17-05351.1996
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Differentiation of Schwann Cells in Transgenic Mice with IncreasedPMP22Gene Dosage

Abstract: An intrachromosomal duplication containing the PMP22 gene is associated with the human hereditary peripheral neuropathy Charcot-Marie-Tooth disease type 1A, and PMP22 overexpression as a consequence of increased PMP22 gene dosage has been suggested as causative event in this frequent disorder of peripheral nerves. We have generated transgenic mice that carry additional copies of the pmp22 gene to prove that increased PMP22 gene dosage is sufficient to cause PNS myelin deficiencies. Mice carrying approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
146
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 229 publications
(160 citation statements)
references
References 56 publications
(56 reference statements)
11
146
0
3
Order By: Relevance
“…Although controversial, the altered PMP22 gene dosage in CMT1A appears to be reflected by increased levels of PMP22 mRNA in Schwann cells (Yoshikawa, 1994) and PMP22 protein in peripheral myelin (Vallat, 1996; see also Hanemann, 1994). In mouse models alone, altered dosage of normal myelin genes causing myelination defects has now been described for the major compact myelin proteins in both the CNS and PNS, namely for MBP (Shine et al, 1992), P0 (Giese et al, 1992;Martini et al, 1995), PLP (Nave, 1994), and PMP22 (Adlkofer et al, 1996;Magyar et al, 1996;Sereda et al, 1996). In addition, apparent gain of function, as well as dominant negative mutations, has been identified among this group of proteins (Warner et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Although controversial, the altered PMP22 gene dosage in CMT1A appears to be reflected by increased levels of PMP22 mRNA in Schwann cells (Yoshikawa, 1994) and PMP22 protein in peripheral myelin (Vallat, 1996; see also Hanemann, 1994). In mouse models alone, altered dosage of normal myelin genes causing myelination defects has now been described for the major compact myelin proteins in both the CNS and PNS, namely for MBP (Shine et al, 1992), P0 (Giese et al, 1992;Martini et al, 1995), PLP (Nave, 1994), and PMP22 (Adlkofer et al, 1996;Magyar et al, 1996;Sereda et al, 1996). In addition, apparent gain of function, as well as dominant negative mutations, has been identified among this group of proteins (Warner et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Various spontaneous and transgenic rodent strains have revealed that PMP22 is involved in the initial spiralling of myelin in early development, the determination of myelin thickness, and the maintenance of myelin and axons of peripheral nerves (Suter et al, 1992a,b;Adlkofer et al, 1995;Magyar et al, 1996;Sereda et al, 1996). In vitro results further suggest that PMP22 is also involved in the control of Schwann cell proliferation and apoptosis (Fabbretti et al, 1995;Zoidl et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…We studied 9 PMP22 ϩ/0 mice at age 375-426 d and 14 PMP22 ϩ/ϩ mice at age 358 -408 d, using previously described techniques (Adlkofer et al, 1995;Magyar et al, 1996). In brief, mice were anesthetized with a neuroleptic/analgesic combination (Hypnorm; Janssen, Beerse, Belgium).…”
Section: Animals and Determination Of Genotypementioning
confidence: 99%
“…Rat CMT1A model and C22 or C3 mouse models with over‐expression of Pmp22 have all developed slowed conduction velocities and dysmyelination 30, 31, 32…”
Section: Rodent Models For Cmt1amentioning
confidence: 99%